TEACHER GUIDANCE AND COUNSELING STRATEGY IN IMPROVING STUDENT DISCIPLINE AT MADRASAH ALIYAH RAUDLATUL HUDA AL-ISLAMY - Ika Mawarni; Amrulloh Khoirul Ma'arif; Syeh Al Ngarifin (STIT Pringsewu, 2023)
ABSTACT As an educational institution, madrasah have some of the same problems as educational institutions in general. One problems that occur in madrasah is the level of student delinquency which affects the discipline of madrasas. For this case researchers conducted research through a qualitative approach, namely by direct observation of the field, conducting interviews and collecting dokumentation of existing problems, then presented in the form of data that is more easily understood by oneself and others. From the results of the research, guidance and counseling teachers have their own strategies to overcome student delinquency problems, so this strategy is used as an effort to improve student discipline. Efforts or strategies made by BK teachers to prevent delinquency and to increase student discipline, namely by displaying school rules and reading them at every flag ceremony, controlling and going around class, conveying information and providing motivation through activities such as IPNU and IPPNU then giving warnings or reprimand. Differences in character are a challenge for BK teachers to understand in depth one by one student. Keywords: teacher guidance and counseling strategies, student discipline